2022
DOI: 10.1007/s13555-022-00773-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Healthcare Resource Utilization Among Patients with Atopic Dermatitis: A Retrospective Cohort Study Using German Health Claims Data

Abstract: Introduction: Atopic dermatitis (AD) is a common inflammatory skin disease. Many patients are initiating a systemic therapy, if the disease is not adequately controlled with topical treatment only. Currently, there is little real-world evidence on the AD-related medical care situation in Germany. This study analyzed patient characteristics, treatment patterns, healthcare resource utilization and costs associated with systemically treated AD for the German healthcare system.Methods: In this descriptive, retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
3
1
0
Order By: Relevance
“…18 Moreover, TCIs are reimbursed only when initiated by a dermatologist, directing initiations to secondary care. Consistent with previous studies, 2,14,19 the results showed low level of phototherapy and systemic therapy use among AD patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…18 Moreover, TCIs are reimbursed only when initiated by a dermatologist, directing initiations to secondary care. Consistent with previous studies, 2,14,19 the results showed low level of phototherapy and systemic therapy use among AD patients.…”
Section: Discussionsupporting
confidence: 91%
“…This was also supported by the long time to the potential next systemic treatment. The use of SCS was notably low (0.4% in all patients and 1.5% in patients with severe AD) compared with data from other countries, 12,15,19 but in line with the European guidelines 8…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We speculate that restrictions in medical care due to racial and ethnic aspects, which are relevant in other parts of the world ( 31 ), are not likely to have a relevant impact in our study. We rather suspect that the major cause for insufficient current medical care is a disappointment with medical care due to either delay in diagnosis [e.g., HS ( 32 )], a limited efficacy of approved drugs [e.g., HS ( 13 )], or the doctors’ hesitation to prescribe expensive, albeit highly effective drugs ( 33 , 34 ). Regarding prescriptions, the most prevalent barriers to prescription of biologics reported by physicians in Germany in 2017 were the high cost, the low reimbursement and the fear of recourse ( 35 ).…”
Section: Discussionmentioning
confidence: 99%